Radiohead and the global movement for change : "pragmatism not idealism" - Rose, Phil, 1969- (Fairleigh Dickinson University Press ; Co-published with the Rowman and Littlefield Publishing Group, Incorporated, 2016)
This book investigates the fascinating and important work of the British group Radiohead, named by Time Magazine among its Top 100 Most Influential People of 2008, and focuses particularly on their landmark recording OK Computer (1997). Probing the band's exploration of the crucial issues surrounding contemporary technological development, especially as it relates to the concern of human survival, Radiohead and the Global Movement for Change is essentially a work of criticism that in its analysis combines what is known as 'musical hermeneutics' with the media ecology perspective.